PENGUPASAN KULIT BUAH DENGAN PERENDAMAN AIR PANAS TERHADAPRENDEMEN,SIFATFISIKOKIMIA DAN ORGANOLEPTIKJUSTOMAT - Rendi Dwi Cahyo; Raswen Efendi; Netti Herawati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Processedtomatojuicealongwiththeskinproducesalesssofttextureandtestessour,soit needs to be peel. One way to make tomato make tomato skin peel easily.This study aims toobtain the right soaking time for peeling tomato skin for manufacture of tomato juice.Thisresearch was conducted experimentally using a completely randomized design (CRD) consisting offour treatments and four replications.The treatments in this study were TS1 = without heating :TS2 = heating temperature of 80ºC, for 20 seconds, TS3 = heating temperature of 80ºC, for 25seconds, TS4 = heating temperature of 80ºC, for 30 seconds.The results of the study wereanalyzed using Analysis of Variance (ANOVA).If the calculated F is greater than the F table, theDuncan Multiple Range Test (DMRT) will be continued at the 5% level.The results showed thathealting timehad a significant effect on yield, vitamin C content, total dissolved solids, viscosity,color, and hedonic sensory test.Mean while, there was no significant difference (P>0.05) in thetaste of tomato juice.Based on the analysis of physico-chemical properties, yield, and sensory testof tomato juice, the treatment chosen in this study was heating at 80ºC for 25 seconds (TS3) with ayield of 95,74%, vitamin C content of 10.63%, total dissolved solids 13,80 Brixº, viscosity 380,967cP, and sensory ratings have a red color (2.45), slightly tomato-scented aroma (2.80), sour taste(2.35),andoverallratinglike (2.35). Keywords:tomatoes,heatingtime,tomatojuice